Empirical Test of Pharmacy Staff-Patient Relationship Quality Model in Public Health Center: Structural Equation Modeling-Partial Least Square Approach - Prasojo Pribadi; Widarika Santi Hapsari; Mia Annida Amalia (Universitas Sebelas Maret, 2022)
Patient Centered Care (PCC) is a new paradigm in health care service that places patients as centers of care. Patient Centered Care in the relationship quality model consists of three components, namely: (1) pharmacist participative behavior, (2) interpersonal communication and (3) patient participative behaviour. This study aims to empirical testing of pharmacy staff-patient relationship quality model among BPJS patients in the Public Health Centers (PHC) Magelang Region. This type of research is quantitative correlational with cross sectional approach. The sample used was 255 respondents. The sampling method in this study was non-probability sampling with purposive sampling technique. Hypothesis testing were used Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of research are interpersonal communication have a positive effect on commitment relationships and the quality of communicative relationship. (p <0.05). Patient participation behavior has a positive effect on the commitment relationships and the quality of communicative relationships (p <0.05). Pharmacy staff participation behaviour has a positive effect on the commitment relationships the quality of communicative relationships (p <0.05). PHC need to improve pharmacy staff clinical performance, therefore that pharmacy staff can provide services pharmaceuticals that meet the targets and standards set.